2010
DOI: 10.1002/pmic.200900055
|View full text |Cite
|
Sign up to set email alerts
|

The effect of simvastatin on the proteome of detergent‐resistant membrane domains: Decreases of specific proteins previously related to cytoskeleton regulation, calcium homeostasis and cell fate

Abstract: Cell death induced by over-activation of glutamate receptors occurs in different neuropathologies. Cholesterol depletors protect from neurotoxic over-activation of glutamate receptors, and we have recently reported that this neuroprotection is associated with a reduction of the N-methyl-D-aspartate subtype of glutamate receptors in detergent-resistant membrane domains (DRM). In the present study we used comparative proteomics to further identify which proteins, besides the N-methyl-D-aspartate receptor, change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…In agreement with previous reports (22,23), our DRM fraction was highly enriched in cytoskeletal proteins and furthermore, many were reduced by PTRF expression (Table II). This in- Western blotting was performed to analyze changes in protein expression by probing with antibodies against PTRF, caveolin-1, KLK-6, and IL-6.…”
supporting
confidence: 93%
“…In agreement with previous reports (22,23), our DRM fraction was highly enriched in cytoskeletal proteins and furthermore, many were reduced by PTRF expression (Table II). This in- Western blotting was performed to analyze changes in protein expression by probing with antibodies against PTRF, caveolin-1, KLK-6, and IL-6.…”
supporting
confidence: 93%
“…Prohibitins are primarily thought of as a mitochondrial proteins but have previously been detected in lipid raft preparations from various cell types [19,20, 21]. Furthermore, it has recently been shown that palmitoylation of prohibitin facilitates its translocation to the plasma membrane where it interacts with the lipid raft protein EHD2 [22].…”
Section: Resultsmentioning
confidence: 99%
“…PHB1 (51,53), PHB2 (56), and PHB1⅐PHB2 complexes (14,57) associate with plasma membrane lipid rafts that are believed to modulate many intracellular signaling events. Overexpression of PHB1 in 3T3-L1 fibroblasts up-regulates basal ERK MAPK signaling, leading to adipogenesis (58).…”
Section: Discussionmentioning
confidence: 99%